Visual and Keeping Quality of Stored Bulb Onions as Affected by Harvest and Postharvest Treatments - Irene N. Kiura; Bernard M. Gichimu; Felix Rotich (International Journal of Agronomy)
Productivity of onion (Allium cepa L.) in Kenya is constrained by postharvest losses. Most postharvest strategies applicable to onions are applied singularly, and therefore, their combined effects have not been well studied. This study evaluated the combined effects of harvesting stage, curing period, and time of topping on postharvest visual and keeping quality of red bulb onions. The study was carried out in Yatta Sub-County, Machakos County, Kenya. The experimental design was a split-split plot laid out in 3 × 3 × 2 factorial arrangement. The treatments consisted of harvesting stage (25%, 50%, and 75% top fall), curing period (none, 1 week, and 2 weeks) and time of topping (before and after curing). After three months of storage, the bulbs were assessed for visual and keeping quality using incidences of skin rots, skin colour, percent of marketable bulbs, residual weight of the bulbs after curing, and days to 50% sprouting. Bulbs that were harvested at 75% top fall and cured for one or two weeks before topping were found to have significantly better visual and keeping quality. Although seasonal variations were significant for some of the parameters assessed, a similar trend was observed in both seasons. The study recommends harvesting of onions at 75% top fall and curing for at least one week before topping for enhanced visual and keeping quality of harvested bulb onions.